Assessing spatiotemporal and functional organization of mitochondrial networks - Kurz, Felix T.; Aon, Miguel A.; O’Rourke, Brian; Armoundas, Antonis A. (Mitochondrial bioenergetics, 2018)
The functional and spatiotemporal organization of mitochondrial redox signaling networks can be studied in detail in cardiac myocytes and neurons by assessing the time-resolved signaling traits of their individual mitochondrial components. Perturbations of the mitochondrial network through oxidative stress can lead to coordinated, cluster-bound behavior in the form of synchronized limit-cycle oscillations of mitochondrial inner membrane potentials. These oscillations are facilitated by both structural coupling through changes in the local redox balance and signaling microdomains and functional coupling that is yet poorly understood. Thus, quantifiable measures of both coupling mechanisms, local dynamic mitochondrial coupling constants and functional clustering coefficients, are likely to offer valuable information on mitochondrial network organization. We provide step-by-step methodologies on how to acquire and assess these measures for inner membrane potential fluorescence fluctuations in laser-scanning two-photon microscope recordings of cardiac myocytes and neurons, that can be applied to other tissues as well.